Analisis Praktik Pengasuhan Orang Tua Berbasis Developmentally Appropriate Practice (DAP) di Lingkungan Desa Muliorejo Kec. Sunggal-Deli Serdang - Yusanita Sitanggang; Srinahyanti Srinahyanti (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This study aims to find out what are the parenting behaviors given by parents when interacting with children based on Developmentally Appropriate Practice (DAP) parenting practices and what obstacles parents face in implementing DAP-based parenting practices. This research is a type of qualitative research. The research subjects in this study totaled 8 people including 7 parents who had early childhood and 1 village head in the Muliorejo Village Environment, Kec. Sunggal - Deli Serdang. Collecting data using interviews, observation, and documentation. Analysis of the research data used a qualitative descriptive method, namely presenting the data in written form and explaining what it was in accordance with the data obtained from the research results. Checking the validity of the data in this study used the triangulation technique. The results of this study indicate that there are various forms of parenting behavior given by parents in DAP-based practices. There are several parenting behaviors given by parents when interacting with children, namely behavior given by parents who silence and persuade when their child is crying, parental awareness behavior in providing support to children when children complete their tasks (school homework), parental behavior that not giving their children opportunities to express feelings or things that make children cry, behavior given by parents when fostering children's self-confidence, and behavior by parents in providing a sense of security to children. Parents in the Muliorejo Village Environment, Kec. Sunggal-Deli Serdang has obstacles in implementing DAP-based parenting practices. The obstacles are the influence of the environment, the economy in the family and parents' education.